2008
DOI: 10.1007/s11761-008-0026-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and framework-based design of a fault-tolerant web information system for m-health

Abstract: The e-health domain has the objective to assist and manage citizens' health. It concerns many actors like patient, doctors, hospitals and administration. Current and forthcoming generations of application will be web based and will integrate more and more mobile devices. In such application domain, called m-health, dependability is a key notion. In addition, more and more functionalities of such systems will be implemented as services for providing qualities like adaptability and maintainability. This paper pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Belli et al [18] have shown fault taxonomy on the basis of sequencing pattern of the graph-based approach; positive sequencing faults, negative sequencing faults. Balbastro et al [19] have focused on the error during service delivery as a latent error and dormant fault.…”
Section: Some Observed Faults In Soa Based Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Belli et al [18] have shown fault taxonomy on the basis of sequencing pattern of the graph-based approach; positive sequencing faults, negative sequencing faults. Balbastro et al [19] have focused on the error during service delivery as a latent error and dormant fault.…”
Section: Some Observed Faults In Soa Based Systemsmentioning
confidence: 99%
“…Transaction isolation fault [19] Synchronized transactional fault tolerant approach Transaction evolving from a flat transaction, transactions with savepoints, nested transactions -A mechanism for handling exceptions in a synchronized way -FT (Fault Tree) technique for providing correct service in case of long-lived transaction Service unavailability fault [27], [24] Modelling approach -Temporal unavailability of service = Estimated execution time < end available time -Temporal service unavailability -Analysis impact region and applying repair strategies: replacement, re-composition, and renegotiation -Calculates temporal negative impact, inconsistent and satisfied OR consistent and unsatisfied OR inconsistent and unsatisfied.…”
Section: Fault Fault Tolerant Approach Fault Assumption/cause Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…SOA specific fault can be categorized as publishing fault, discovering fault, composition fault, binding fault and execution fault according the SOA life cycle stages as proposed by [6]. Service unavailability fault [7] [8], byzantine fault [9] [10], prescribed policy violation [11], timeout exception [12], SLA (Service Level Agreement) claim fault [13], latent errors and dormant faults [14], adaptation faults [15], interaction faults [16], network traffic [17] of service-oriented computing faults are noted to be highly emphasized faults by the researchers.…”
Section: Introductionmentioning
confidence: 99%